(untitled) (Tempo e Argumento, 2020)
This paper presents the proposal of "Nosotras contamos. Un recorrido por la obra de autoras de historieta y humor gráfico de ayer y hoy" an initiative to build feminist genealogy in the field of humorous cartoons and graphic sequential arts. The initial project is framed in gynocritical approaches from which it is proposed to rediscover an art made by women (Showalter, 1981) and feminist genealogy as a research methodology (Restrepo, A., 2016). The results were reflected in a website, a traveling exhibition and a catalog that presented a tour of the work of more than eighty female authors between 1930 and today and involved a process of research in periodicals, collections and archives. The proposal led us to question the category "woman" and to use "authorship" as a category that contains feminities that produce in the field of comics and cartoons. This allowed us to reconstruct a map that links the emancipatory struggles of women, lesbians, transvestites / transgender people and non-binary people with the creation of a graphic document in popular circulation magazines. Part of this process is compiled on the website www.feminismografico.com. Keywords: Comic. Feminist Genealogy. Authorship.